Financial Guarantees of the Regional Budget are Growth Potential for the Investments in Fixed Capital - Kabanov, Vadim Nikolaevich; Zhilnikov, Aleksandr Yuryevich; Zablotskaya, Tatyana Yuryevna (Economy of Regions, 2018)
In accordance with the existing standards applied to estimate the performance of regional public authorities, the quantitative indexes comprise such variables as ‘amount of fixed investments’ and ‘the tax revenues of regional budgets’. To the authors’ opinion, these variables are in mathematical relations. We assume that such relations can be used to assess the financial tools, which are at the disposal of regional public authorities. We have developed a methodology for quantitative evaluation of the economic performance of the financial instruments, which are at the disposal of regional public authorities and can impact the economic growth. The research is based on the comparative statistical analysis of the National Statistical Monitoring System concerning the economic development of Belgorod region. As a result, we have determined the acceptable potential for the increase of the Belgorod region’s budget guarantees assigned for the implementation of major investment projects. We have obtained the dependency of the tax revenues of regional budgets on the fixed assets productivity (the fixed capital or property used to generate income). Our technique allows to evaluate the amount of fiscal revenues of the budget of a federal subject of the Russian Federation depending both on the financial guarantees assigned by the regional budgets and on the productivity of fixed assets (capital productivity). The research results show that up-to-date domestic practice in managing the economic growth in the federal subjects of Russia underestimates the financial guarantees performance. The financial guarantee instrument is prioritized for the major investment projects. These projects can ensure the yield from capital investments as many as four, which fosters the increase of the fiscal revenues of regional budgets up to 40 %. We have measured the economic performance of management decisions concerning the choice of financial instruments by regional public authorities. Moreover, the paper presents the projection of the results from each financial instrument application.